Media Motion Graphics Berbasis E-Learning Untuk Meningkatkan Motivasi Belajar Siswa Materi Keanekaragaman Hayati - Ervan Johan Wicaksana; Binanggra Alpa Pebriand; Pramana Atmadja; Wikanso Wikanso (BIOEDUSCIENCE, 2021)
Background: Biology is a pure science that is analytical and systematic. It relates to the reality of the problems experienced by students in the current biology learning process, which is a monotonous way of learning and tends to make students feel bored with the learning process carried out, so that the teaching material delivered by the teacher or educator is difficult to understand by students. This class action research aims to improve student learning motivation on Biodiversity material. Methods: This class action research was conducted in two cycles; the first cycle was carried out with one meeting and the second cycle was carried out with one meeting. Each cycle is the application of Kemmis and Mc Taggart's classroom action research consisting of 4 stages: planning, action, observation, and reflection. Results: The results of this study are an increase in learning motivation of students in each cycle. Conclusions: Based on these results, it can be concluded that the Motion Graphics learning media based on e-learning has succeeded in increasing students' learning motivation on Biodiversity material.